3-Metallierte Enamine als Homoenolate – Eine neue Entwicklung in der Enaminchemie - Hubertus Ahlbrecht (CHIMIA)
The deprotonation of tertiary enamines at C-3 is described. The resulting highly nucleophilic 1-aminoallylic anions 8 react with a large number of electrophiles at C-3 to form homologated enamines 10 (γ-products). By this reaction enamines, normally considered as substitutes for enolates 3 can be used as synthetic equivalents of homoenolates 6. In some cases substituted allylic amines (α-products) are found additionally. NMR- and UV-spectroscopic investigations indicate, that in solution the carbanionic intermediates are contact ion pairs. The regioselectivity of this species depends on internal and external effects. The results are best rationalized assuming that the metal is located close to C-3 and the γ-product is formed by direct (SE2), the α-product by vinylogous electrophilic attack (SE2') on the contact ion pair.